Политика Идентичности и Демократия В Индонезии (Identity Politics and Democracy In Indonesia) - Setiawan, Refly; Valentinovna , Kolesova Olga (Jurnal Cita Hukum, 2025)
The article presents an analysis of the implementation of identity policy in Indonesia in its correlation with the democratic principles proclaimed by the government. The importance of having a state identity in the modern political situation is substantiated. An understanding of identity is provided from a scientific perspective, and the specifics of understanding identity in Indonesian national policy are explored. The reliance on understanding identity is based on national specifics, including traditions, state laws, symbols, and the constitution that prescribe its interpretation. The connection between identity policy and the proclaimed democracy is shown. An assumption is made about the potential for further identity formation in the country. The specifics of how the Indonesian government interprets democratic principles are highlighted. The main principles of democracy are given - "Trisila", formed by the first president of the Republic of Indonesia, Sukarno. The positioning of the political and economic aspects of democracy is emphasized. The triggers of conflicts in Indonesian society are recorded. An understanding of the specifics of "identity policy" and "political identity" is provided. The connection between democratic culture and regional political cultures is revealed. The difficulties of implementing identity politics in the regions are shown. Cultural elements such as religions, ethnic groups, and ideologies are used as instruments for promoting regional interests. Political and ethnic “gaps” are understood as defining structural elements of Indonesia’s identity politics.